MALLBA: a software library to design efficient optimisation algorithms. (26th April 2007) - Alba, Enrique; Luque, Gabriel; Garcia-Nieto, Jose; Ordonez, Guillermo, Guillermo Leguizamon
In this paper we discuss on the MALLBA framework, a software tool for the resolution of combinatorial optimisation problems using generic algorithmic skeletons implemented in C++. Every skeleton in the MALLBA library implements an optimisation method (exacts, metaheuristics and hybrids) and provides three different implementations for it: sequential, parallel for Local Area Networks and parallel for Wide Area Networks. This paper introduces some aspects about the software design of the MALLBA library, details of the most recent implemented skeletons and offers computational results for a scheduling problem to illustrate the utilisation of our library.